Human Capital, Management Quality, and the Exit Decisions of Entrepreneurial Firms - He, Shan; Li, C. Wei (Journal of Financial and Quantitative Analysis, 2016)
We model the employee incentive problem jointly with a firm’s exit decision. Our model predicts that firms in industries where human capital is important are more likely to go public and use high-powered, stock-based compensation. We also show that the higher the management quality, the more likely a firm is to go public than to be acquired. Regarding life cycle, a firm with high capital intensity and/or high management quality will choose to go public at a younger age.